Study of Utilizing Wawonii River Materials as an Alternative Aggregate for Road Subbase - Anafi Minmahddun; Muh. Handy Dwi Adityawan (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
This paper presents the results of tests on the characteristics of the Bobolio River material which has the potential to be used as an alternative aggregate for road subbase. Characteristic tests carried out include sieve analysis, specific gravity and absorption testing of coarse and fine aggregate, abrasion testing and compaction testing and Laboratory CBR. The results of testing the specific gravity and absorption of coarse and fine aggregates showed that the specific gravity of the coarse aggregate was 2.65 grams/cm3 (2.4-2.8 grams/cm3) and the absorption was 3.31% (maximum 5%). The specific gravity of fine aggregate is 2.51 grams/cm3 (1.6-3.2 grams/cm3) and absorption is 0.42% (maximum 2%). Abrasion testing obtained a wear value of 23% (0-40%). CBR value at 95% maximum density value is 20.50% (min 50%). The characteristic test results show that all parameters meet the 2018 Bina Marga specifications except the CBR value. Even if the CBR value does not meet specifications, Bobolio River material with good wear value can be mixed with material from other sources to meet the required CBR value.